Behavioural response of honeybees (Apis mellifera scutellata Lep.) to wild pollinators on sunflowers (Helianthus annuus L.) - Nicolson, Sue W. (University of Pretoria, 2013)
Dissertation (MScAgric)--University of Pretoria, 2010.